TANGGUNG JAWAB PEMERINTAH KOTA TANGERANG DALAM MENGATASI KEBAKARAN TPA RAWA KUCING BERDASARKAN PERATURAN DAERAH NOMOR 2 TAHUN 2022: Responsibility Tangerang City Government in Overcoming Rawa Kucing Landfill Fire Based on Regional Regulation Number 2 of 2022 - Farhan Ramadhany Putra Suryana; Eko Primananda (Reformasi Hukum Trisakti, 2025)
Tangerang has the Rawa Kucing landfill in Neglasari, which recently experienced a fire. Handling this fire is the responsibility of the Tangerang City Government, especially the Environmental Agency. The problem formulation of this research is how the responsibility of the Tangerang city government in handling the Rawa Kucing landfill fire and what are the obstacles of the Tangerang city government in handling the Rawa Kucing landfill fire based on Perda No. 2 of 2022 concerning Waste Management. The research methods used are juridical and normative approaches, with qualitative data analysis. Conclusions are drawn through deductive logic, based on Law Number 23 of 2014 concerning Regional Government and Tangerang City Regional Regulation Number 2 of 2022 concerning Waste Management. The results and conclusions show that the Tangerang City Government has not fully addressed the problem of waste management properly, especially in the open dumping system, and the handling of fires at the Rawa Kucing Waste Landfill is not running quickly due to various obstacles faced.